Respostas

2013-06-03T17:46:52-03:00

a) 
5(x - 2y + 1) = x - 8y + 7
2x - y/3 = 1/5

Simplificando:

5x - 10y + 5 = x - 8y + 7
2x - y/3 = 1/5 (x15)

4x - 2y = 2 [*]
30x - 5y = 3 

Multiplicando a primeira por -15, a segunda por 2 e somando, temos:

-60x + 30y = -30
60x - 10y = 6 
-----------------------------
20y = -24

y = -24/20 = -6/5

Substituindo em [*]

4x - 2y = 2
4x - 2 * -6/5 = 2
4x + 12/5 = 2
4x = 2 - 12/5
4x = 10/5 - 12/5
4x = -2/5
x = (-2/5) / 4
x = -2/20
x = -1/10

=======================================…
b)
2x + y = x + 4
2x + y = x + 2y + 1

Simplificando:

x + y = 4 [**]
x - y = 1

Multiplicando a primeira por -1 e somando, temos:

-x - y = -4 
x - y = 1
----------------
-2y = -3
y = 3/2

Substituindo em [**]:

x + y = 4
x + 3/2 = 4
x = 8/2 - 3/2
x = 5/2

1 2 1